Quaternary time scales for the Pontocaspian domain: Interbasinal connectivity and faunal evolution - Krijgsman, W.; Tesakov, A.; Yanina, T.; Lazarev, S.; Danukalova, G.; Van Baak, C.; Agustí, J.; Alçiçek, M.; Aliyeva, E.; Bista, D.; Bruch, A.; Büyükmeriç, Y.; et al. (Elsevier BV, 2019)
© 2018 The Authors The Pontocaspian (Black Sea - Caspian Sea) region has a very dynamic history of basin development and biotic evolution. The region is the remnant of a once vast Paratethys Sea. It contains some of the best Eurasian geological records of tectonic, climatic and paleoenvironmental change. The Pliocene-Quaternary co-evolution of the Black Sea-Caspian Sea is dominated by major changes in water (lake and sea) levels resulting in a pulsating system of connected and isolated basins. Understanding the history of the region, including the drivers of lake level and faunal evolution, is hampered by indistinct stratigraphic nomenclature and contradicting time constraints for regional sedimentary successions. In this paper we review and update the late Pliocene to Quaternary stratigraphic framework of the Pontocaspian domain, focusing on the Black Sea Basin, Caspian Basin, Marmara Sea and the terrestrial environments surrounding these large, mostly endorheic lake-sea systems.